PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS AUTOPLAY PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM: PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS AUTOPLAY PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Devi Sela Eka Selvia; Imam Syafe’i; Aizi Tri Utami Rozer (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this research and development is to produce Autoplay-based learning media in PAI and Budi Pekerti subjects on fard prayer material as an innovation and a solution to the problem of students' understanding of fard prayer material and can add. This research uses the Research and Development (R&D) method with the ADDIE model which consists of 5 stages, namely Analysis, Design, Development, Implementation, and Evaluatin. The subjects of this research and development are seventh grade students at SMP Negeri Satu Atap 1 Sragi. The techniques used in collecting data are interviews, validation questionnaires, and feasibility questionnaires. The results of the feasibility test by material expert validators 1 and 2 were 77.1% and 87.5% respectively, media experts 87.5%, with the criteria “Very feasible”. The feasibility response test by educators obtained a percentage of 92.5%, the feasibility response of students in the large group was 86.25% with the criteria “very feasible” at SMP Negeri Satu Atap 1 Sragi and it can be stated that Autoplay Media is feasible to use in learning.